Stromal cell-derived factor 1 (SDF-1) increases the number of telocytes in ex vivo and in vitro assays - Sanches, Bruno Domingos Azevedo; Tamarindo, Guilherme Henrique; da Silva, Alana Della Torre [UNESP]; Amaro, Gustavo Matheus [UNESP]; dos Santos Maldarine, Juliana; dos Santos, Vitória Alário [UNESP]; Guerra, Luiz Henrique Alves [UNESP]; Baraldi, Carolina Marques Bedolo [UNESP]; Góes, Rejane Maira [UNESP]; Taboga, Sebastião Roberto [UNESP]; Carvalho, Hernandes F. (Springer Nature, 2023)
Telocytes are interstitial cells that are present in various tissues, have long cytoplasmic projections known as telopodes, and are classified as CD34+ cells. Telopodes form extensive networks that permeate the stroma, and there is evidence that these networks connect several stromal cell types, giving them an important role in intercellular communication and the maintenance of tissue organisation. Data have also shown that these networks can be impaired and the number of telocytes reduced in association with many pathological conditions such as cancer and fibrosis. Thus, techniques that promote telocyte proliferation have become an important therapeutic target. In this study, ex vivo and in vitro assays were conducted to evaluate the impact on prostatic telocytes of SDF-1, a factor involved in the proliferation and migration of CD34+ cells. SDF-1 caused an increase in the number of telocytes in explants, as well as morphological changes that were possibly related to the proliferation of these cells. These changes involved the fusion of telopode segments, linked to an increase in cell body volume. In vitro assays also showed that SDF-1 enriched prostate stromal cells with telocytes. Altogether, the data indicate that SDF-1 may offer promising uses in therapies that aim to increase the number of telocytes. However, further studies are needed to confirm the efficiency of this factor in different tissues/pathological conditions.
Keywords: Cancer; CD34; Cell proliferation; Conditioned medium; CXCR4; Fibrosis; Prostate explants; Sclerosis; Telopode network; Tissue organisation